PELAKSANAAN REHABILITASI PECANDU NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA: Aria Suntoro - admin, admin; Hariz Hamdallah, Muhammad Andika (Reformasi Hukum, 2018)
Narcotics rehabilitation is carried out so that every narcotics addict can recover and be accepted back in the community. The implementation of narcotics rehabilitation has been regulated in Law No. 35 of 2009 concerning Narcotics, especially in Articles 54, 55 and 103 of the Narcotics Act. Basically sanctions stipulated in the Narcotics Act adhere to a double track system, namely in the form of criminal sanctions and sanctions for action. Although there are already rules and regulations governing narcotics rehabilitation, the implementation must be manifested. Because the regulation does not really benefit if there is no movement and is not carried out properly according to the applicable law. The method used in this thesis is a normative method that examines or discusses theories that exist in the legal literature. This research was conducted to describe the Implementation of Rehabilitation of Narcotics Addicts based on Law Number 35 of 2009 concerning Narcotics, to find out what factors caused someone to commit narcotics abuse and explain the Islamic view of the perpetrators of narcotics abuse. This research can be concluded that there are still many narcotics abuse victims who do not carry out the mandatory reporting program to the authorities, the factor of someone using narcotics and being victims of narcotics abuse due to personal, socio-cultural, narcotics availability and still lacking in the Narcotics Law.